'A Hope Raised and then Defeated'? the Continuing Harms of Irish Abortion Law. Issue 1 (March 2020) - de Londras, Fiona
Irish legislative engagement with abortion law reform has never been framed by recognition of the rights of pregnant women, girls and other people. Rather, where it has taken place at all, it has always been foetocentric and punitive, exceptionalising abortion and conceptualising law as a means of discouraging it. In important ways, the post-repeal landscape has failed to break decisively with this orientation. While in 2018 there was certainly more discussion of women's entitlement not to be exiled from the country in order to make decisions about reproduction, the framing that dominated legislative and government discourses of abortion law reform was one in which the 'problem' being addressed was such that unsafe medication, exclusion from formal medical systems, and the undeserved punishment of people who had received diagnoses of fatal foetal conditions in the course of their 'much wanted pregnancies' were the focus. There was little or no engagement in legislative politics with the right to choose, reproductive agency, reproductive justice or the moral standing of pregnant people as ethical decision makers when it came to their pregnancies. As a result, post-repeal abortion law reform was more about managing risk than maximising agency. I will argue that this underpins and partly explains the shortcomings of the new law: the Health (Regulation of Termination of Pregnancy) Act 2018 ('HRTPA 2018'). Within that new legal regime, I argue, pregnant people continue to lack decisional security when it comes to their reproductive lives and are exposed to significant constitutional and dignitary harms as a result.